Structural, electrical, dielectric and magnetic behavior of Gd1−xBixFe1−yZryO3 nanoparticles for advanced technological applications. Issue 7 (August 2015) - Kousar, Tehmina; Ahmad, Iqbal; Khan, Muhammad Azhar; Nasar, Gulfam; Shahid, Muhammad; Shakir, Imran; Warsi, Muhammad Farooq
Abstract: Gd1− x Bi x Fe1− y Zr y O3 nanoparticles were synthesized via micro-emulsion route with different molar concentrations of Bi +3 ( x ) and Zr +4 ( y ). The values of x and y were kept in the range 0.00, 0.15, 0.30, 0.45 and 0.60. The characterizations were done by the thermo-gravimetric analysis (TGA), X-ray Diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The average particle size was ~50 nm. The effect of Bi 3+ and Zr 4+ contents on electrical, dielectric and magnetic parameters were studied. The DC resistivity measurements showed at certain Bi 3+ and Zr 4+ contents, more than two fold increase in electrical resistivity from 68×10 8  Ω cm to 150×10 8  Ω cm. The magnetic measurements showed the paramagnetic nature of Gd1− x Bi x Fe1− y Zr y O3 nanoparticles. The electrical and magnetic properties of these nanoparticles suggested that these materials are potential candidates for the fabrication of telecommunication and switching devices.